2017
DOI: 10.1159/000480734
|View full text |Cite
|
Sign up to set email alerts
|

Women Serum Concentrations of the IL-10 Family of Cytokines and IFN-γ Decrease from the Third Trimester of Pregnancy to Active Labor

Abstract: Labor is regarded as increased myometrial activity with a regular contractility pattern. At this final stage of pregnancy, myometrial quiescence is lost, accompanied by altered immune homeostasis. It is well known that the interleukin (IL)-10 family of cytokines modulates immunological responses mainly in epithelial cells, including the endometrium. To investigate their inflammatory profile during labor, we performed a longitudinal study in a group of healthy pregnant women (n = 20) with uncomplicated pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
3
10
1
Order By: Relevance
“…Wang et al 37 found increased level of IL-18 in pregnant women compared to non-pregnant women confirming our results of increased levels of IL-18 throughout pregnancy and postpartum compared to baseline. A few other longitudinal studies are in accordance with our result of a decrease in IL-10 between late pregnancy and postpartum 16,20,36 . In addition, another study found stability in IL-10 postpartum measured at multiple time-points 8 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Wang et al 37 found increased level of IL-18 in pregnant women compared to non-pregnant women confirming our results of increased levels of IL-18 throughout pregnancy and postpartum compared to baseline. A few other longitudinal studies are in accordance with our result of a decrease in IL-10 between late pregnancy and postpartum 16,20,36 . In addition, another study found stability in IL-10 postpartum measured at multiple time-points 8 .…”
Section: Discussionsupporting
confidence: 92%
“…Chemokines control the homeostasis of the immune cells and represent a pro-inflammatory mediator. One of the most studied chemokines longitudinally in pregnancy is the IL-8 protein (also named CXCL-8) where several studies found no change during pregnancy 16,17,25 or from late pregnancy to postpartum 8,25 . In line with our U-shaped pattern between the time-points of IL-8 is Christian et al 23 who found decreased level of IL-8 during pregnancy but increased level postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). In a recent study, we reported that the systemic downregulation of several members of the IL‐10 cytokines family may play an important role in the stimulation of the myometrial smooth cells associated with uterine contractions of a woman in active labor . Accordingly, this immune downregulation seems to agree with the well‐reported functional progesterone withdrawal occurring at parturition .…”
Section: Parturition and The Caipsupporting
confidence: 72%
“…In a recent study, we reported that the systemic downregulation of several members of the IL‐10 cytokines family may play an important role in the stimulation of the myometrial smooth cells associated with uterine contractions of a woman in active labor . Accordingly, this immune downregulation seems to agree with the well‐reported functional progesterone withdrawal occurring at parturition . It is well known that the ANS plays a major regulatory role of multiple complex physiological systems in the organism and it acts as a part of the neuroimmune response to sterile and nonsterile tissue injuries via the CAIP .…”
Section: Parturition and The Caipsupporting
confidence: 69%